2019
DOI: 10.1007/s10534-019-00209-0
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of recombinant buffalo lactoferrin and monoferric lobes and their cytotoxic effect on buffalo mammary epithelial cells

Abstract: Lactoferrin (Lf) has been involved in diverse type of cellular activities and its biochemical properties are species specific. Lf is a bilobal molecule in which each lobe binds with one Fe 2? /Fe 3? ion. A lot of physiological effects of Lf are regulated by its iron binding and release properties; however these properties are species-specific. To understand the ironbinding, thermal stability and cytotoxic effect of buffalo Lf (buLf) and contribution of individual Nand C-terminal lobes therein, buLf and the tru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…LF is a multifunctional protein with varying activities: promoting intestinal iron absorption, anti-inflammation, antibacterial, etc. [ 17 , 18 ]. This protein is an iron-binding glycoprotein with two lobes, which can reversibly bind to Fe 2+ /Fe 3+ [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…LF is a multifunctional protein with varying activities: promoting intestinal iron absorption, anti-inflammation, antibacterial, etc. [ 17 , 18 ]. This protein is an iron-binding glycoprotein with two lobes, which can reversibly bind to Fe 2+ /Fe 3+ [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…LF has a polypeptide chain with about 690 amino acid residues and forms a basically symmetrical bilobal structure, while each lobe can reversibly bind to Fe 2+ /Fe 3+ [ 1 , 17 , 18 ]. It was reported that iron binding can obviously affect the biological functions of LF.…”
Section: Introductionmentioning
confidence: 99%